Characterization of nanoparticle electrocatalysts using X-ray absorption spectroscopy - Nebojša Marinković; Radoslav R. Adžić (Zaštita Materijala)
X-ray absorption spectroscopy (XAS) is a non-destructive spectroscopic technique commonly used with synchrotron radiation source and measures the changes of absorption coefficient as the function of the x-ray energy. Its unique power is that it can reveal the internal structure of nanoparticles, even if the particle is made up of several elements. By analyzing the results, interatomic distances and coordination numbers for each element are obtained, and their values and relationships indicate whether the elements in the nanoparticle are in a homogeneous solution, physically separated, or form a core-shell particles in which certain elements are mostly located in the core, and the other in the shell. The latter type of nanoparticles is of particular interest for the electrocatalysts as it reduces the precious metal content in the nanoparticles by replacing the precious metal in the the nanoparticles' core with less expensive alternatives. This paper describes the internal structure characterization of the nanoparticle electrocatalysts by in situ XAS, and gives certain examples of systems composed of two or three metals.